MEMBANGKITKAN SPIRITUALITAS DAN MEMPOSISIKAN PUISI SEBAGAI OBAT JIWA; KAJIAN PSIKOLOGI SPIRITUAL PUISI SHOBIR POER - Andika Hendra Mustakim (Wanastra: Jurnal Bahasa dan Sastra, 2014)
The aims of this research are explore spiritualism in poems of Shobir Poer and dig the meaning of poem for the human spirituality. By the textual analysis, the researcher finds the poems of Shobir Poer has the spiritual atmosfire which focus on issue of religion and belief. The poems able to enrich the spirituality of the reader or the listener. Moreover, the poems also become a soul medicine for the reader and listener. Using dictions and rhymes, adding specific topics, poems of Shobir Poer, ask the reader to rise and believe to the guide of the God.